Wide‐Bandgap Double Perovskites with Multiple Longitudinal‐Optical Phonon Scattering. (25th February 2022) - Wang, Liangling; Zheng, Wei; Vitale, Francesco; Zhang, Xiangzhou; Li, Xiuling; Ji, Yanchen; Liu, Zhen; Ghaebi, Omid; Plass, Christian T.; Domes, Robert; Frosch, Torsten; Soavi, Giancarlo; et al.
Abstract: Alloyed lead‐free double perovskites display intense photoluminescence, are environmentally friendly, and their devices show long‐term operation. Thanks to these properties, which make them excellent warm white‐emitting materials, they have recently received great attention in lighting applications. An important factor to tune the optical properties of alloyed lead‐free double perovskites is the presence of self‐trapped excitons. Here, it is demonstrated that in lead‐free double perovskites, the strong electron–phonon coupling plays a crucial role in the generation of self‐trapped excitons. The strong electron–phonon coupling is confirmed by a large Huang–Rhys factor and by the presence of multiphonon transitions. In particular, sharp emission lines superimposed on the broad photoluminescence emission band of one of these samples (Cs2 Ag0.6 Na0.4 InCl6 0.5%Bi) are observed; these are due to the strong coupling of longitudinal‐optical phonons with excited electronic states caused by the tetragonally distorted AgCl6 octahedrons. Such a strong coupling of longitudinal‐optical phonons to electrons can effectively modulate the photophysical properties of alloyed double perovskites, and its understanding is, thus, of paramount importance for the design of future optoelectronic devices. Abstract : The Huang–Rhys factor of Cs2 Ag0.6 Na0.4 InCl6 0.5%Bi is 36.5, indicating strong electron–phonon coupling, which is necessary for self‐trapped exciton formation. In particular, sharp emission lines super‐imposed on the broad photoluminescence emission band are observed; these are due to the strong coupling of longitudinal‐optical phonons with excited electronic states.